Saturday

April 19, 2014

April 19, 2014

Posted by **anonymous** on Saturday, May 25, 2013 at 10:07am.

= -x^4+3x^3+6

2) (3n^3+n^2-n-4)+(5n^3-4n^2+11)

= 8n^3-3n^2-n+11

- polynomials am i doing it right? -
**MathMate**, Saturday, May 25, 2013 at 10:25amYou're on the right track...

1. expand it and write it out when it is a subtraction:

(x^4+7x^3+7)-(2x^4-4x^3+1)

= x^4+7x^3+7) -2x^4+4x^3-1

= -x^4 +*11*x^3 + 6

2. space out your terms to avoid losing some of them.

(3n^3 + n^2 -n -4)+(5n^3 -4n^2 + 11)

= 3n^3 + n^2 -n -4 + 5n^3 -4n^2 + 11

= 8n^3 - 3n^2 -n + 7

- polynomials am i doing it right? -
**anonymous**, Saturday, May 25, 2013 at 10:41amfor #1 i did

(x^4+7x^3+7)-(2x^4-4x^3+1)

= x^4+7x^3+7-2x^4-4x^3-1

= -x^4+3x^3+6

so why is it wrong?

- polynomials am i doing it right? -
**Mercy**, Saturday, May 25, 2013 at 10:45ambecause you see that when you expanded the polynomials after the -2x^4 yu have a - instead of a positive because recall that when the brackets expand - and - = +.

That is the only thing you did wrong.

Good luck! you are on the right track though.

- polynomials am i doing it right? -
**anonymous**, Saturday, May 25, 2013 at 10:48amok thank you

- polynomials am i doing it right? -
**Mercy**, Saturday, May 25, 2013 at 10:52amno problem:)

**Related Questions**

Math - Can someone please check my answers below for accurateness? The ...

bobpursley,math - about this problem , I figured it out and i did get the answer...

math - find the difference when (-2x^2+7x-5) is subtracted from (3x^2-4x+2). -2x...

algebra - thank everyone that site helped but now i just have to practice. for ...

Math/Algebra - Find each sum or difference (3x^2 + 7x- 2)+ (2x^2 - 3x + 4) ...

Math - Write these in factored form? 12 +6x x+x+x+6 x^2 + 3x x^2 + 4x +3 Combine...

math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...

Math - Solve the Equations 142=58-7x 2x+96=-44-3x -26=-7x+4(2x-4) 7x+5(-4x-4)=-...